Radical nephrectomy with inferior vena cava tumor thrombectomy in Mayo III–IV renal cell carcinoma: a retrospective single-center study - Shabunin, Alexey; Grekov, Dmitry; Karpov, Alexey; Drozdov, Pavel; Karabach, Yuri; Levikov, Dmitry; Glushenko, Igor; Bagatelia, Zurab; Veliev, Evgeny; Bogdanov, Andrey (Frontiers in Surgery, 2025)
BackgroundTumor thrombus extending into the inferior vena cava (IVC) in patients with renal cell carcinoma (RCC), particularly at Mayo levels III and IV, presents a major surgical challenge. Although systemic treatments are evolving, surgery remains the mainstay of management. The role of cardiopulmonary bypass (CPB) in this setting is not clearly defined.MethodsWe retrospectively analyzed 20 patients with RCC and Mayo level III–IV IVC tumor thrombus who underwent radical nephrectomy with IVC thrombectomy at our center between 2017 and 2024. Preoperative workup included MRI, contrast-enhanced CT, and transthoracic/transesophageal echocardiography. CPB was used selectively in five patients with tumor extension into and adherence to the right atrium. Postoperative complications were classified using the Clavien–Dindo system. Survival was assessed with Kaplan–Meier analysis and Cox regression.ResultsMedian age was 61 years (IQR 51–72), and 70% were male. Level IV thrombus was present in 60% of patients, and 40% had distant metastases. Median operative time was 370 minutes and median blood loss was 2,500 mL. Postoperative complications occurred in 20% of patients, with one in-hospital death (5%). Median hospital stay was 11 days. The 1-, 3-, and 5-year overall survival rates were 66.7%, 41.6%, and 34.6%, respectively. Distant metastases were associated with lower survival (HR 2.48; p = 0.005), while immuno-targeted therapy improved outcomes (HR 0.69; p = 0.035).ConclusionRadical nephrectomy with IVC thrombectomy in patients with advanced tumor thrombus can be performed safely with good long-term outcomes in selected cases. Careful preoperative imaging, intraoperative echocardiography, and the selective use of CPB are key to minimizing risks. These findings support a tailored surgical approach based on thrombus level and clinical condition. Further prospective studies are needed to refine surgical indications and clarify the role of systemic therapy.